PERLINDUNGAN TERHADAP PEMEGANG SAHAM MINORITAS BERDASARKAN UNDANG-UNDANG NOMOR 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS - Pangestu, Lintang Caesar; Noer, Zakiah; Dara (Judge : Jurnal Hukum, 2026)
This study analyzes the legal reconstruction of minority shareholder protection under Law No. 40 of 2007 in Indonesia, focusing on special rights and fiduciary duties. Using normative legal research with statute and case approaches, the study identifies a disconnect between formal regulations and substantive justice, often leading to "abuse of majority," as seen in the PT Sumalindo Lestari Jaya Tbk case. Findings indicate that shareholders below the 10% threshold remain vulnerable due to information asymmetry and high litigation costs. To strengthen Good Corporate Governance (GCG), this research proposes a systemic restructuring: lowering derivative suit thresholds, granting explicit legal recognition to Shareholders' Agreements (SHA), and mandating cumulative voting. Additionally, optimizing fiduciary duty enforcement requires clearer judicial interpretations of the Business Judgment Rule and the expansion of the "piercing the corporate veil" doctrine. These reforms are vital to mitigate oppressive majority actions and enhance the global competitiveness of Indonesian corporations.